A A CASE STUDY ON ROLE OF CHAVYADI CHURNA SATTU FOR AGNIDEEPAN AND WEIGHT REDUCTION: A CONCEPTUAL AND CLINICAL APPROACH - Bhavsar, Dr Pranita (Ayurline: International Journal of Research in Indian Medicine, 2026)
Obesity and impaired digestive fire (Agnimandya) are increasingly prevalent health concerns in modern society, often associated with sedentary lifestyle, irregular dietary habits, and metabolic disturbances. Ayurveda emphasizes that proper digestion and metabolism, governed by Agni, form the foundation of health. Chavyadi Churna and Sattu are classical formulations known for their role in improving Agni, enhancing metabolism, and supporting healthy weight management. The present study aims to explore the role of Chavyadi Churna along with Sattu in Agnideepan (digestive fire stimulation) and weight reduction, while correlating Ayurvedic principles with contemporary understanding of digestion and metabolism. Chavyadi Churna is composed of key ingredients such as Chavya (Piper retrofractum), Pippali (Piper longum), Shunthi (Zingiber officinale), and Maricha (Piper nigrum), which are predominantly Katu Rasa, Ushna Virya, and Laghu-Tikshna in Guna. These pharmacological properties help in Amapachana, stimulation of Jatharagni, and regulation of Kapha-Medodhatu. Sattu, being a roasted cereal/legume-based preparation, is light, protein-rich, and easily digestible. It provides sustained energy without aggravating Kapha, making it suitable for weight management diets. When administered together, the combination promotes improved digestion, reduces Ama accumulation, enhances metabolic efficiency, and supports gradual fat mobilization.